Anisotropic Thermal Expansion of Transparent Cellulose Nanopapers - Hirano, Takayuki; Mitsuzawa, Kana; Ishioka, Shun; Daicho, Kazuho; Soeta, Hiroto; Zhao, Mengchen; Takeda, Masaaki; Takai, Yoshihiro; Fujisawa, Shuji; Saito, Tsuguyuki (Frontiers in Chemistry, 2020)
We report the anisotropic thermal expansion of a transparent nanopaper structure comprising cellulose nanofibers (CNFs). The coefficient of thermal expansion (CTE) of the nanopaper in the out-of-plane direction was 44.6 ppm/°C in the temperature range of 25‒100°C, which is approximately five times larger than its CTE in the in-plane direction in the same temperature range (8.3 ppm/°C). Such a strong anisotropy in thermal expansion is mainly attributable to the anisotropic CTE values of single CNFs in the fiber axis and cross-sectional directions. We observed anisotropic thermal expansion even in a bioplastic composite containing only 2.5% w/w CNFs.